Generation of crystal structures using known crystal structures as analogues. Issue 4 (16th July 2016) - Cole, Jason C.; Groom, Colin R.; Read, Murray G.; Giangreco, Ilenia; McCabe, Patrick; Reilly, Anthony M.; Shields, Gregory P.
Abstract : An investigation into using shape‐similarity of molecules to generate putative crystal structures. Abstract : This analysis attempts to answer the question of whether similar molecules crystallize in a similar manner. An analysis of structures in the Cambridge Structural Database shows that the answer is yes – sometimes they do, particularly for single‐component structures. However, one does need to define what we mean by similar in both cases. Building on this observation we then demonstrate how this correlation between shape similarity and packing similarity can be used to generate potential lattices for molecules with no known crystal structure. Simple intermolecular interaction potentials can be used to minimize these potential lattices. Finally we discuss the many limitations of this approach.